Abortion stigma as a social process. (January 2020) - Millar, Erica
Abstract: 'Abortion stigma' has become a critical concept in abortion scholarship, activism, policy and broader discourse. The concept of abortion stigma is, however, poorly defined and scholarship tends to use the concept in ways that reaffirm the individual as its source and location. The majority of research frames abortion stigma as a set of values, beliefs and judgements that flow from stigmatisers to the stigmatised, who are then believed to possess a negatively-valued identity. This article reorients abortion stigma scholarship away from Goffman to Foucault, arguing that abortion stigma should be reframed as a classificatory form of power that works through designating relations of difference. Stigma is one of many processes through which abortion is made intelligible and is contingent and contested. This reframing has implications for the type of questions that scholars can and must ask when examining abortion stigma. Highlights: Abortion stigma is generally defined in terms of individual-level beliefs, behaviours and attributes Abortion stigma should be reframed as a social process